Infantile Cutaneous Langerhans Cell Histiocytosis Presenting as Benign Skin Lesions: Clinical Pitfalls and Diagnostic Clues - Lintzeri, Dimitra Aikaterini; Constantinou, Andria; Vogt, Annika; Blume-Peytavi, Ulrike (Dermatology Practical & Conceptual, 2026)
Introduction: Langerhans cell histiocytosis (LCH) is a rare but potentially life-threatening hematologic disorder characterized by a wide spectrum of skin manifestations that may mimic a variety of common neonatal and pediatric diseases.Objectives: To raise awareness of the broad clinical spectrum of cutaneous manifestations important for early recognition.Methods: Herein, we present seven cases of LCH with diverse skin manifestations, disease type, and course of disease. Results: Dermatological examination was key in suspecting LCH in all cases, enabling prompt oncological evaluation with skin signs preceding other organ involvement. Skin manifestations ranged from isolated to widespread skin rashes. Common lesions included erythematous, reddish-brown, or skin-colored crusted or scaly papules or maculopapular lesions. However, plaques, patches, vesicles, and urticarial lesions may also occur.Conclusions: Timely dermatological consultation should be sought in cases of non-resolving, therapy-resistant skin lesions and an unclear diagnosis.